Calidad de vida en adultos institucionalizados con parálisis cerebral infantil. - Martínez-Traver, Laura; Cervera Gasch, Águeda (Enfermería Global, 2020)
Introduction: Cerebral palsy is considered a group of permanent developmental disorders that cause limitations in daily activity. One of the complications in people with cerebral palsy is the decrease in quality of life. Objective: The objective of this study is to know the quality of life for institutionalized adults with infantile cerebral palsy and to know if there are differences in the quality of life index based on functional characteristics. Method: Cross-sectional descriptive observational study in institutionalized adults with infantile cerebral palsy performed in the APCA and ASPROPACE centers between March and September 2017. The San Martín questionnaire was administered to measure the Quality of Life, Gross motor classification system, Barthel questionnaire, Scale CFCS to measure motor function, physical dependence, level of communication and relate them with sociodemographic and clinical variables. The selection of the participants was carried out by random stratified sampling. It was approved by the centers' addresses. Results: Participants were 39 people with an average age of 32.54 years. The overall average score of the San Martin questionnaire was 102.97 points. The most affected dimensions were material wellbeing, personal development and social incluison. No statistical significance was obtained in the overall score of the questionnaire based on the secondary variables. Conclusions: The results of this study have shown that the quality of life of adults with cerebral palsy in the subjects studied is good.